A Quantitative Model to Calculate Gas Sealing Capacity and Design Sealing Parameters for Premium Connection. (24th February 2020) - Xu, Honglin; Yang, Bin
Abstract : The present research studies about sealability of premium connection almost focus on qualitative description by sealing contact stress distribution, which is not convenient for sealing capacity evaluation and sealing parameter design. This paper proposes a quantitative model to calculate directly gas sealing capacity of cone to cone premium connection, different from the usual finite element method with testing, which combines the elastic thick wall cylinder interference fit theory for calculating sealing stress with the gas sealing criterion obtained from Murtagian's experimental results. With the proposed model, the effects of pipe wall thickness, seal cone taper, radial sealing interference, and axial sealing length on the gas sealing capacity have been investigated. Furthermore, the gas sealing capacity envelope curve based on radial sealing interference and axial sealing length is also calculated and a new sealing parameter design method is proposed for cone to cone premium connection. The results show that the internal upset pipe is good for sealability, and increasing both radial sealing interference and axial sealing length can significantly enhance gas sealability while seal cone taper has an unobvious effect on it. To meet sealing capacity, the designed sealing parameter combination ( δ d, L d ) should be located in the upper right region of the gas sealing capacity envelope curve.